Wirkungen der Abgeltungsteuer auf die Kapitalallokation: Anregungen für eine Reform - Christian A. Conrad (Wirtschaftsdienst, 2012)
Die Abgeltungsteuer auf Einkünfte aus Wertpapieranlagen wurde 2009 in Deutschland eingeführt. Damit sollte die bisherige Quellensteuer vereinfacht und die Steuerflucht ins Ausland durch den einheitlichen, relativ niedrigen Steuersatz verhindert werden. Christian Conrad sieht jedoch steuerliche Fehlanreize und leitet daraus Handlungsempfehlungen für die Politik ab. – – The flat tax was introduced in Germany in 2009. It is imposed on income from portfolio investment, such as interest and dividends, but also on gains from stock sales. As this paper shows, the tax causes a massive distortion of after-tax returns in favour of debt capital. The financing structure of companies will therefore change in favour of debt capital. The tax discriminates German investors against foreign investors and the profitability of equity decreases strongly. The withholding tax has serious conceptual weaknesses that cause a massive misallocation of capital and thus a lasting damage to growth in Germany. Several recommendations for the necessary amendments are outlined in the article.
Keywords: G12; H21; K34; 330; Abgeltungssteuer; Kapitalertragsteuer; Steuerwirkung; Investition; Deutschland